2012
DOI: 10.1143/jpsj.81.011005
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Imaging Scanning Tunneling Microscopy Studies of Electronic Structure in the Superconducting and Pseudogap Phases of Cuprate High-TcSuperconductors

Abstract: One of the key motivations for the development of atomically resolved spectroscopic imaging scanning tunneling microscopy (SI-STM) has been to probe the electronic structure of cuprate high temperature superconductors. In both the d-wave superconducting (dSC) and the pseudogap (PG) phases of underdoped cuprates, two distinct classes of electronic states are observed using SI-STM. The first class consists of the dispersive Bogoliubov quasiparticles of a homogeneous d-wave superconductor. These are detected belo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
157
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(170 citation statements)
references
References 119 publications
(312 reference statements)
11
157
0
2
Order By: Relevance
“…Moreover, we demonstrate that the dFF-DW modulations at E = −∆ 1 (filled states) occur with relative phase π compared to those at E = ∆ 1 (empty states). Finally, we show that the conventionally defined dFF-DW Q corresponds to scattering between the 'hot frontier' regions of momentum-space beyond which Bogoliubov quasiparticles cease to exist [30][31][32] . These data indicate that the cuprate dFF-DW state involves particle-hole interactions focused at the pseudogap energy scale and between the four pairs of 'hot frontier' regions in momentum space where the pseudogap opens.…”
mentioning
confidence: 93%
“…Moreover, we demonstrate that the dFF-DW modulations at E = −∆ 1 (filled states) occur with relative phase π compared to those at E = ∆ 1 (empty states). Finally, we show that the conventionally defined dFF-DW Q corresponds to scattering between the 'hot frontier' regions of momentum-space beyond which Bogoliubov quasiparticles cease to exist [30][31][32] . These data indicate that the cuprate dFF-DW state involves particle-hole interactions focused at the pseudogap energy scale and between the four pairs of 'hot frontier' regions in momentum space where the pseudogap opens.…”
mentioning
confidence: 93%
“…1,2 Because the pseudogap phase appears in the proximity of half filling, it is probably related to Mott insulators 3,4 (precisely, charge-transfer insulators 5 ). Experimentally, the pseudogap phase presents various features distinct from an ordinary Fermi liquid.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Rotational symmetry breaking (or nematic order) similar to the stripe phase is observed, and the oxygen sites between copper atoms are involved. 2,20 (3) Charge orders or charge density waves are observed in resonant X-ray scattering experiments. [21][22][23] (4) (π, π)-folded (shadow) bands appear in ARPES spectra, and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8,9 STS has revealed that the cuprates have a spatially inhomogeneous electronic structure, including modulations in the LDOS and superconducting gap magnitude. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the d-wave superconducting phase, the LDOS modulations can arise from quasiparticle interference (QPI), due to the scattering of wave-like quasiparticles off impurities. 12,15,22,[25][26][27] The wavevectors of the modulations can be determined from the Fourier transform of the LDOS.…”
Section: Introductionmentioning
confidence: 99%